How Revisit Intention Infuenced by Service Quality in a Cafeteria? - Lazuardi, Saddam Maulana; Perwangsa Nuralam, Inggang (Profit: Jurnal Adminsitrasi Bisnis, 2025)
This study aims to directly determine the impact of service quality on customer satisfaction and word of mouth and revisit intention. In addition, this study also aims to determine the effect of customer satisfaction and word of mouth on revisit intention. We also investigate the mediating effect of customer satisfaction and word of mouth on the relationship between service quality and revisit intention. The type of research used is explanatory research with a quantitative approach. The population in this study were Universitas Brawijaya students who were consumers of the Universitas Brawijaya Creative Land Cafeteria, with a sample of 210 respondents obtained through a purposive sampling technique. The data collection method used an online questionnaire, and the data analysis technique used Partial Least Square-Structural Equation Modeling (PLS-SEM) using SMARTPLS Version 3.2.9 software. The testing results show that service quality directly affects customer satisfaction, word of mouth, and revisit intention. Moreover, customer satisfaction and word of mouth affect revisit intention. Testing the indirect effect shows that service quality significantly affects revisit intention through customer satisfaction and word of mouth.